Socialna inovacija za boj proti diskriminaciji oseb z oviranostmi v grajenem okolju - Sendi, Richard (Urbani izziv, 2014)
The rights of persons with disabilities to barrier-free access and equal opportunities are guaranteed by numerous documents at the international and national levels, but various studies and daily experience show that these legal provisions have not always been implemented in practice. Persons with disabilities continue to experience numerous barriers in the urban environment. This situation shows that current approaches to eliminating environmental barriers are inadequate and that there is an urgent need to search for alternative, more effective solutions. This article presents such a novel solution, premised on the hypothesis that significant progress in this area will be achieved only through restructuring the roles of the major stakeholders. I am thus proposing a reversal of roles, suggesting the introduction of a bottom-up approach as opposed to the current ineffective top-down approaches. In order to facilitate such a bottom-up approach an interactive internet portal have been designed that is presented and describedin this article as a "web forum". Based on a thorough review of the literature on the notion of "social innovation", it is argued that the suggested new approach is a social innovation, an attribute that qualifies it as an effective mechanism that will lead to eventually achieving barrier-free environments and consequently eliminating discrimination against persons with disabilities in the living environment.
Keywords: architecture; arhitektura; arhitekturne ovire; bivalno okolje; diskriminacija; funkcionalno ovirani ljudje